Impact of a structured training program on agility, strength, and sprint performance in U-13 soccer players - Baze, Andi; Delia, Bashkim; Muca, Gentjan; Derhemi, Laura (Edelweiss Applied Science and Technology, 2025)
The aim of this study was to evaluate the effect of a 12-week intervention training program on motor skills and health parameters in youth soccer players (boys). A total of 57 participants (mean age = 12.5 years) in Tirana, Albania, were randomly assigned to an intervention group (n = 28) or a control group (n = 29). The intervention group followed a structured training program (3 times/week, 15 minutes per session) focusing on running technique, coordination, reaction time, jumping, and multidirectional sprinting, while the control group continued with their routine training. Anthropometric measurements (body weight, height, and waist circumference) and motor performance tests (agility 10 × 5m, agility T-test, sprint 10m and 20m, standing long jump, and standing high jump) were conducted pre- and post-intervention. Statistical analysis revealed no significant differences between groups in body height, weight, and BMI (p > 0.05), although a significant reduction in waist circumference was observed (p = 0.024). The intervention group showed significant improvements in agility (10 × 5m and T-test), sprint performance (20m sprint, p < 0.05), and lower limb strength (standing long jump, standing high jump, and countermovement jump, p < 0.05). No significant differences were found for the 10m sprint test. These findings suggest that a 12-week structured training program effectively enhances agility, sprint performance (20m), and lower limb strength in young soccer players.